NTP Server Design as a Mitigation of Time Difference at Perum LPPNPI Kendari Branch - Pambudiyatno, Nyaris; Kurniawan Putra, Muh. Rayhan; Pragolo, Argo (Nusantara Publisher, 2024)
In the world of aviation, it takes the right time, time synchronization is very important for the aviation system. If the time of the flight telecommunication facility is out of sync or out of sync, the flight data will be chaotic, so it is not known when the aircraft will land. If the time is not synchronized, data on accident incidents will be difficult to find. This research method uses an Microcontroller connected to the Network Time Protocol Server through internet media, then the Network Time Protocol Server generates time data in the form of Coordinate Universal Time. The Microcontroller functions as a server on the device that will perform time synchronization, and the Network Time Protocol Server data has accurate time accuracy. In the event of a time shift it will be compensated by the Microcontroller.